2013
DOI: 10.1021/es402323c
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Hydroxylated Polychlorinated Biphenyls (OH-PCBs) in Sediment from a Lake Michigan Waterway and Original Commercial Aroclors

Abstract: Hydroxylated polychlorinated biphenyls (OH-PCBs) were measured in surficial sediment from Indiana Harbor and Ship Canal (IHSC), East Chicago, IN and five original Monsanto Aroclors. These compounds were measured using gas chromatography with tandem mass spectrometry (GC-MS/MS) and certified standards that allowed us to identify 65 individual or co-eluting congeners. Concentrations in the sediment ranged from 0.20 to 26 ng/g dry weight. Profiles of most samples were similar and were dominated by mono- to penta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(87 citation statements)
references
References 44 publications
4
82
1
Order By: Relevance
“…PCB fractions were spiked with 0.6 ng of 13 C-labeled PCB surrogate standards and internal standards were added before instrument analysis. Samples were analyzed using gas chromatography-tandem mass spectrometry (GC-MS/MS) (Marek et al, 2013a). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PCB fractions were spiked with 0.6 ng of 13 C-labeled PCB surrogate standards and internal standards were added before instrument analysis. Samples were analyzed using gas chromatography-tandem mass spectrometry (GC-MS/MS) (Marek et al, 2013a). …”
Section: Methodsmentioning
confidence: 99%
“…Recent studies also found OH-PCBs in sediments (Marek et al, 2013a) and human waste has been proposed as a source to surface waters (Ueno et al, 2007). Our group previously demonstrated that OH-PCBs are important metabolic products of PCB 11 and PCB 3 in rats and are excreted in urine and feces (Hu et al, 2013; 2014; Dhakal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aroclor and non-Aroclor PCBs and their hydroxylated metabolites (OH-PCBs) have been measured in people around the world including children. 2, 2629 Although OH-PCBs are recognized as human 28, 30 and plant 31 metabolites of PCBs, they are also emerging as abiotic environmental contaminants of water, 32 sediment and Aroclors, 33 and outdoor air. 34 Exposure of school-age children to PCBs and OH-PCBs is particularly concerning because these compounds are carcinogenic to humans, 35 target the endocrine system, 36, 37 and are linked to neurodevelopmental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…24 It has also been suggested that OH-PCBs could be formed in the atmosphere through reaction with hydroxyl radicals or could originate from commercial formulations. 5,6 As transformation products of PCBs, OH-PCBs are widely dispersed in the environment, and they have been detected in a variety of samples, including air, water, sediments, and animal tissues. 68 OH-PCBs have raised environmental concerns because of their reported toxicity for a variety of organisms, sometimes even higher than the toxicity of parent PCBs.…”
Section: Introductionmentioning
confidence: 99%